C22 SYNCOPE UNIT AND REMOTE CONTROL IN THE ERA OF COVID–19 PANDEMIC: EXPERIENCE OF A SINGLE CENTER. (18th May 2022) - Ferrieri, A; Dentico, A; Epicoco, G; Carretta, F; D'Agostino, C; Carretta, D
Abstract: Introduction: During the pandemic, many Syncope Units were closed due to inclusion of them and staff in Covid departments. In our experience, in order to meet the numerous requests of patients suffering from syncope, the care strategy was chosen to carry out all outpatient procedures within a single access. The use of this protocol made it possible to satisfy user requests, breaking down all barriers, including the fear of Covid–19. Materials and Methods: The procedural process used in this period at our O.U. was: initial evaluation, execution of Active Stand Test, carotid sinus massage and implantation of loop recorder in a single access. Immediately after implantation, the patient was equipped with remote monitoring. Patients without events were followed only remotely and underwent telephone follow–up approximately every 3 months to update the center on their general state of health and any symptoms. In patients with events, the individual events were examined by the cardiologist and, by telephone follow–up, the presence of symptoms was assessed, correlating the recorded event with the reported symptom. These were subsequently summoned to the clinic. Results: With this operating model in the years 2020/2021 we managed 53 patients in the Syncope Unit. Of these, 5 underwent PM implantation for loop recorder's remote monitoring of the paroxysmal AVB, and one patient, for the detection of major ventricular arrhythmias, was protected with Life Vest pending completion of cardiological screening. The remaining patients, thanks to the remote control, are constantly followed at home and monitored with periodic telephone follow–up. Conclusions: In line with the literature, also in our ER there was a notable reduction in accesses for syncope. Our operating model was virtuous as it served to decongest the ER and the wards, concentrating all patients with syncope in our Syncope Unit and also reducing the number of tests necessary to arrive at an etiological diagnosis of syncope. The Covid–19 pandemic has accelerated the transformation process of the Syncope Unit which is no longer just an elective place for the diagnosis of syncope, but also a fundamental reference for the remote control of ICM wearers.